Face to face the relationship between receiver apprehension and social distance in a teacher-student dyadic interaction - Colina, Madelyn C. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
Includes bibliographical references and appendices.
Thesis (B.A. in Speech Communication)
Keywords: Communication in education; Teacher-student relationships; Interaction analysis in education